Prevalence of chronic kidney disease and the incidence of acute kidney injury in patients with coronary artery disease in Mumbai, India - Pavan Malleshappa; Bharat V Shah (Heart Views, 2015)
Background and Objective: To determine the prevalence of chronic kidney disease (CKD) and incidence of acute kidney injury (AKI) in patients with coronary artery disease (CAD) demonstrated on coronary angiography. Materials and Methods: Totally, 125 patients admitted to Lilavati Hospital and Research Centre, Mumbai, with CAD were included in the study. Results: Left anterior descending artery was the major vessel involved (40%), followed by a circumflex artery (21.6%). 49 out of 125 (39.2%) were found to have underlying CKD. 69% (34) of these CKD patients developed AKI. 21 out of 34 patients who developed AKI required hemodialysis. Only 47.1% (16 out of 34) of CKD patients had complete recovery, 29% had partial recovery, and 23% had no recovery of their renal function from AKI. Statistically significant number of patients in CKD group had no recovery from AKI as compared to non-CKD group (23.5% vs. 0%). Conclusion: Our study concludes that there is a very high prevalence of CKD (39.2%) in patients with CAD and AKI is a very important complication (38.4%) in these patients. Considering such a high prevalence of CKD, nephrology referral must be considered in patients with abnormal urinalysis, spot urinary protein to creatinine ratio and in patients whose creatinine clearance is <60 ml/min.